SUPERVISI KEPALA SEKOLAH UNTUK MENINGKATKAN KOMPETENSI PEDAGOGIK SPIRITUAL PENDIDIK - Nurti Budiyanti; Asep Abdul Aziz; Dikdik Sunandar; Mohamad Erihadiana (Sekolah Tinggi Agama Islam Al Hidayah Bogor, 2021)
The welfare of a nation is determined by the quality of education. Similarly, the quality of education is determined by the quality of teacher competencies, especially spiritual pedagogical competencies. The development of the spiritual pedagogical competence of teachers in Islamic boarding schools is a must, considering the teacher as the spearhead in determining the processes and learning outcomes. Likewise, principals as a supervisor has a strategic role in making use of teachers in school. This study focuses on analyzing the approaches, strategies, and implications of the principal's supervision as a means of improving the spiritual pedagogical competence of teachers in PPI 1-2 Bandung. In addition, this study also employed a qualitative approach in the form of case study. The data were taken from documentation and informants determined by snowball sampling. The data were collected using interviews, observation, and study documentation. The data were analyzed through reducing data, presenting data, and drawing conclusions. Then, the data were validated by triangulating the sources. The results of this study are that (1) Principal supervision strategy is carried out through the effective application of academic supervision with conceptual, interpersonal and technical skills. (2) The principal's supervision approach uses a direct, indirect and collaborative approach. In this case, what is studied is related to mastering learning theory and learning principles that educate, developing curriculum related to the subjects being taught, and utilizing information and communication technology in learning that is taught. (3) The implications for schools are the creation of a conducive school atmosphere and effective learning by updating the character of the curriculum, policies and rules that contain spiritual values. Then, the implication for teachers is the creation of a conducive school atmosphere and effective learning by disciplining administration, expanding resources and teaching materials, utilizing technology and information, applying the Quranic method, applying educational media, and establishing an evaluation and enrichment program that functions to improve spiritual quality of students. Thus, the improvement of teacher spiritual pedagogical competence can be applied well in order to produce students who have Islamic character.